2013
DOI: 10.14257/ijast.2013.61.01
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Near Infrared light Application Combined with Aerobic Exercise on Excessive Abdominal Fat and Obesity

Abstract: This study was conducted to examine the effects of a near infrared-light-emitting diode (NIR-LED) in conjunction with low endurance exercise on obesity and abdominal fat. Twenty-six overweight adolescents aged 14-15 years were divided into an experimental and control group. Participants in the experimental group performed endurance exercise on a treadmill while wearing NIR-LED belts on their abdomens. The exercise intensity, duration, and frequency were 50% VO2 max, 45 min/session and three days per week for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The results of the present study support the previous studies that reported that near-infrared application had a significant effect on lipolysis 9 ) . In addition, the study by Ali et al 6 ) supports the results of the present study, reporting that obese adolescents showed a significant decrease in waist circumference, body fat percentage, and body-mass index compared to the control group when near-infrared rays were irradiated into the abdomen during aerobic exercise. The changes in body composition found in the present study may be due to the following: Several studies have shown that near-infrared light penetrates relatively deeply into the brain and tissues 10 ) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the present study support the previous studies that reported that near-infrared application had a significant effect on lipolysis 9 ) . In addition, the study by Ali et al 6 ) supports the results of the present study, reporting that obese adolescents showed a significant decrease in waist circumference, body fat percentage, and body-mass index compared to the control group when near-infrared rays were irradiated into the abdomen during aerobic exercise. The changes in body composition found in the present study may be due to the following: Several studies have shown that near-infrared light penetrates relatively deeply into the brain and tissues 10 ) .…”
Section: Discussionsupporting
confidence: 90%
“…In a prior study, obese adolescents, wearing an abdominal band that radiated near-infrared rays, performed aerobic exercise for 50 minutes 3 times a week for 4 weeks. It was found that body-mass index (BMI), waist circumference, and fat level were significantly more decreased in the group who were treated with both aerobic exercise and NIR, compared to those who only had aerobic exercise 6 ) . In addition, Mecrea et al investigated the effect of water-filtered infrared-A (wIRA) on local fat reduction during moderate bicycle ergometer endurance exercise, and found greater decrease in the circumferences of waist, hip, and both thighs in the wIRA group relative to the control group 7 ) .…”
Section: Introductionmentioning
confidence: 99%